Characteristics of anthocyanins and bioactive compounds of mio-mio (Coriaria ruscifolia L.) - Barragán Condori, Melquiades (2018)
The Natural dye demand is growing worldwide. This research is about the extracts of the fruits of (mio-mio) Coriaria ruscifolia L., from which little information is available, but we found in them anthocyanic and polyphenolic compounds   which are great interest as bioactive compounds because of their antioxidant capacity. Nowadays, It is known that flavonoids including anthocyanins from (Mio mio) fruit has anticancer properties and other functional properties that made this study a great interest and can be used as a great source of antioxidant as natural dyes. The objective of the present study was to determine the bioactive compounds and antioxidant capacity of (Mio mio) fruit to use in the food industry. The extraction of their pigments were carried out with acidified methanol and into this extract their anthocyanin characteristics were determined by Visible UV spectroscopy, FTIR-ATR, then the composition of their anthocyanins were determined by HPLC. The content of total CAT anthocyanins were determined by differential pH method. This 440.22 (mg of cyanidin 3-glucoside / 100 g) in addition the total content of polyphenols PFT were quantified using the Folin-Ciocalteu method with 1820.41 (mg gallic acid / 100 g). The antioxidant capacity TEAC - ABTS has also been evaluated with 739.92 (µmoltrolox / 100 g). The results of the bioactive compounds and antioxidant capacity of (mio mio) fruit extracts were notably higher than those reported by different similar fruits. This impliesas a conclusion that these fruits can be used as a source of antioxidants in the form of natural dyes. In conclusion, the extracts of (mio-mio) correspond to anthocyanin structures with a high antioxidant capacity, with a promising future for agro-industrial use.